Indikator Kinerja Keuangan yang Memengaruhi Nilai Perusahaan pada Subsektor Konstruksi dan Bangunan - Ajeng Septa Ningsih; Lihan Rini Puspo Wijaya; Endang Asliana (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2025)
This research is an empirical study that aims to examine the influence of a number of financial indicators on company value in the construction and building subsectors listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The indicators analyzed include profitability, free cash flow (FCF), and leverage. This study uses a purposive sampling approach involving 9 issuers and produces 45 observation data. The analysis method used is multiple linear regression to test the relationship between independent variables and company value as measured by Price to Book Value (PBV). The results of the study show that the performance of Return on Assets (ROA) as well as the Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) ratios have a significant effect on increasing the company's value. In contrast, other indicators such as Net Profit Margin (NPM), Free Cash Flow (FCF), and Long-Term Debt to Equity Ratio (LTDtER) did not show a significant influence. These findings indicate that investors prioritize capital utilization efficiency and sound funding structures in assessing the value of a company, compared to free cash flow or net profit margins. This research provides important implications for company management and investors in formulating financial strategies that are oriented towards increasing the company's value in a sustainable manner.